Impact of aquatic acoustic noise on oxidative status and some immune parameters in gilthead sea bream Sparus aurata (Linnaeus, 1758) juveniles. (2nd April 2016) - Filiciotto, Francesco; Cecchini, Stefano; Buscaino, Giuseppa; Maccarrone, Vincenzo; Piccione, Giuseppe; Fazio, Francesco
Abstract: This study evaluated the ambient noise effect of onshore and offshore aquaculture systems on oxidative status and on some immune parameters in gilthead sea bream ( Sparus aurata ) juveniles. The experiment was performed for 40 days, projecting two different playlists of acoustic stimuli: offshore aquaculture noise condition that created the typical acoustic field in proximity of an offshore sea cage for fish farming, using a random sequence of quite sea background and boat noises; and onshore aquaculture noise condition that represented the acoustic field inside an open concrete tank for fish farming. A third group without any acoustic projection was used as a control. After 40 days from the beginning of acoustic noise, fish exposed to the offshore aquaculture condition showed significantly higher levels of total oxidant status, lysozyme activity, antiprotease activity and white blood cells together with a lower albumin/globulin ratio in comparison to fish from the control group; whereas fish exposed to the onshore condition showed analytical data placed between the other groups, though never significantly different. These results demonstrate that the offshore aquaculture noise, and in particular the sea soundscape, adversely influences the oxidative status and the immune function of gilthead sea bream determining a mild stress condition that could affect the sea bream welfare.